2016
DOI: 10.1186/s12913-016-1791-x
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of Australian allied health research in ehealth

Abstract: BackgroundUptake of e-health, the use of information communication technologies (ICT) for health service delivery, in allied health appears to be lagging behind other health care areas, despite offering the potential to address problems with service access by rural and remote Australians. The aim of the study was to conduct a scoping review of studies into the application of or attitudes towards ehealth amongst allied health professionals conducted in Australia.MethodsStudies meeting inclusion criteria publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 58 publications
3
49
0
1
Order By: Relevance
“…Further, some speech pathologists considered direct services such as therapy and assessment to be unsuitable for the telepractice environment. These findings are consistent with other studies that have found that speech pathologists prefer to provide indirect services via telepractice (176,220).…”
Section: Speech-language Pathologists' Experiences Of Providing Telepsupporting
confidence: 93%
See 1 more Smart Citation
“…Further, some speech pathologists considered direct services such as therapy and assessment to be unsuitable for the telepractice environment. These findings are consistent with other studies that have found that speech pathologists prefer to provide indirect services via telepractice (176,220).…”
Section: Speech-language Pathologists' Experiences Of Providing Telepsupporting
confidence: 93%
“…Thus, tertiary Despite an increase in telepractice adoption over time, respondents' self-reported understanding and confidence in telepractice did not change, and very few respondents reported high levels of understanding and confidence. Low levels of confidence have been well-documented among nonusers of telepractice (179,180,220), however, previous studies have also found that SLPs' understanding and confidence usually grows once they start implementing telepractice (183). Careful consideration of reported barriers and facilitators will be required to help increase tertiary SLPs' understanding and confidence in using telepractice with CMC.…”
Section: Speech-language Pathologists' Attitudes Towards Telepracticementioning
confidence: 99%
“…However, some professional anxieties, particularly from specialist assessors, over the quality of care (including accuracy of measurement) and adequacy of training in use of technology were reported. This discrepancy between professional (specialist versus remote) and consumer acceptability with a telehealth alternative has been reported in other studies of health professionals and across diverse consumer populations [11,37] and is clearly a barrier to the uptake of tele-WS assessment that should be anticipated and addressed in any future implementation studies.…”
Section: Discussion Principal Resultsmentioning
confidence: 97%
“…Telehealth initiatives in other areas of healthcare services need to consider broad issues such as the adequacy of infrastructure (wi-fi, availability and compatibility of technology) [14], health professional attitudes, client perspectives and the perspectives of funders on this process to anticipate and mitigate potential barriers to the implementation of telehealth use by allied health professionals [11]. A research informed analysis of ways to address these barriers is an important step in the development of new technologies, or to promote use of existing technologies in safe and effective ways.…”
Section: Defining Telehealth Wheelchair and Seating Assessmentmentioning
confidence: 99%
See 1 more Smart Citation